2018
DOI: 10.1111/evj.13053
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of metabolic traits associated with equine metabolic syndrome in Welsh ponies and Morgan horses

Abstract: Summary Background Equine metabolic syndrome (EMS) is a complex clinical disorder with both environmental and genetic factors contributing to EMS phenotypes. Estimates of heritability determine the proportion of variation in a trait that is attributable to genetics. Objectives To provide heritability estimates for nine metabolic traits associated with EMS in two high‐risk breeds. Study design Retrospective cohort study. Methods High‐density single‐nucleotide polymorphism (SNP) genotype data was used to estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 41 publications
2
26
0
Order By: Relevance
“…Within this cohort, we previously showed that baseline insulin had an h 2 SNP of 0.81 (SD = 0.11), with a mean h 2 SNP of 0.82 (mean SE: 0.12) after random subsetting . In this analysis, the h 2 SNP explained by genomic partitioning was 0.19 (SD = 0.086) or 24% of the total h 2 SNP for baseline insulin.…”
Section: Resultsmentioning
confidence: 57%
“…Within this cohort, we previously showed that baseline insulin had an h 2 SNP of 0.81 (SD = 0.11), with a mean h 2 SNP of 0.82 (mean SE: 0.12) after random subsetting . In this analysis, the h 2 SNP explained by genomic partitioning was 0.19 (SD = 0.086) or 24% of the total h 2 SNP for baseline insulin.…”
Section: Resultsmentioning
confidence: 57%
“…A similar variability between breeds has been demonstrated for insulin sensitivity and related biochemical parameters [194][195][196][197]. A recent study used genome-wide SNP data to estimate heritability of several traits known to be perturbed by EMS (glucose, insulin, measures of insulin sensitivity and dyslipidaemia) and found they were moderately to highly heritable [198]. Again, such within-breed comparisons are valuable but are likely to underestimate the true heritability in the equine population.…”
Section: Genetics Influence Equine Obesity Ems and Laminitismentioning
confidence: 66%
“…SNP-based heritability estimates for traits associated with EMS (e.g., circulating insulin, glucose, ACTH, leptin) have bene reported to be quite high (Norton et al 2018). Genetic factors contributing to risk are also supported by varied rates of prevalence among, and variation in insulin responsiveness by breed (Treiber et al 2006; Bailey et al 2008; Bamford et al 2014).…”
Section: Genetics Of Complex Traitsmentioning
confidence: 99%